The feasibility of using liquid biopsies as a complementary assay for copy number aberration profiling in routinely collected paediatric cancer patient samples. (January 2022) - Van Paemel, Ruben; Vandeputte, Charlotte; Raman, Lennart; Van Thorre, Jolien; Willems, Leen; Van Dorpe, Jo; Van Der Linden, Malaïka; De Wilde, Jilke; De Koker, Andries; Menten, Björn; Devalck, Christine; Vicha, Ales; et al.
Abstract: Background: Paediatric tumours are often characterised by the presence of recurrent DNA copy number alterations (CNAs). These DNA copy number profiles, obtained from a tissue biopsy, can aid in the correct prognostic classification and therapeutic stratification of several paediatric cancer entities (e.g. MYCN amplification in neuroblastoma) and are part of the routine diagnostic practice. Liquid biopsies (LQBs) offer a potentially safer alternative for such invasive tumour tissue biopsies and can provide deeper insight into tumour heterogeneity. Procedure: The robustness and reliability of LQB CNA analyses was evaluated. We performed retrospective CNA profiling using shallow whole-genome sequencing (sWGS) on paired plasma circulating cell-free DNA (cfDNA) and tissue DNA samples from routinely collected samples from paediatric patients (n = 128) representing different tumour entities, including osteosarcoma, Ewing sarcoma, rhabdomyosarcoma, Wilms tumour, brain tumours and neuroblastoma. Results: Overall, we observed a good concordance between CNAs in tissue DNA and cfDNA. The main cause of CNA discordance was found to be low cfDNA sample quality (i.e. the ratio of cfDNA (<700 bp) and high molecular weight DNA (>700 bp)). Furthermore, CNAs were observed that were present in cfDNA and not in tissue DNA, or vice-versa. In neuroblastoma samples, no false-positives or false-negatives were identified for the detection of the prognostic marker MYCN amplification. Conclusion: In future prospective studies, CNA analysis on LQBs that are of sufficient quality can serve as a complementary assay for CNA analysis on tissue biopsies, as either cfDNA or tissue DNA can contain CNAs that cannot be identified in the other biomaterial. Highlights: Overall, concordance between copy number aberrations in tissue and plasma is good. Discordance was associated with low-quality cfDNA samples and localised disease. Copy number aberrations can be unique to either tissue DNA or tumour DNA. No false-positives or false-negatives were seen for MYCN detection in neuroblastoma cases.